TINJAUAN LITERATUR : PENERAPAN KOMPRES DINGIN UNTUK MENGURANGI NYERI DAN HEMATOMA PADA PASIEN POST PERCUTANEOUS CORONARY INTERVENTION (PCI) - Baidhowy, Arief Shofyan; Antarika, Gde Yasa; Sungkono, Sungkono; Rumayara, Abraham Bernadus; Listiani, Listiani (Jurnal Perawat Indonesia, 2021)
Coronary heart disease is a narrowing of blood vessels due to arteriosclerosis and atherosclerosis. Noninvasive intervention to open and widen blood vessels is Percutaneous Coronary Intervention (PCI). Pain and hematoma is the most common microvascular complication following PCI.  One of the measures to reduce pain is by applying cold compress on the affected area. This study aims to determine the affect of cold compress on the  pain and hematoma reduction in post PCI patients. The method used in this study is literature review. Articles in this study is obtained from PubMed, Science Direct, Wiley, ProQuest and Springer Link database  from 2016 to 2021 by using “Percutaneous Coronary Intervention” or “ balloon angioplasty” or “Cardiac Catheterization” and “Application of cold” “Cold Compress” or “Ice bag” or “Ice pack” and “Pain” and “Hematoma”  as key words. The searching for the articles was based on the inclusion and exclusion criteria and followed by review. This study found five articles that were included in the analysis for a literature review. These articles describe the effectiveness of cold compress application on post PCI patients by means of its physiological effects such as blood vessels vasoconstriction, slowing tissue metabolism, increased blood viscosity and local anesthetic. The conclusion of the study is that cold compress proved to be effective in reducing pain and hematoma in post PCI patients.